Microsurgical Clipping of Giant Saccular Middle Cerebral Artery Aneurysm: A Case Report - Karki, Mohan; Roka, Yam Bahadur (Birat Journal of Health Sciences, 2022)
Giant saccular middle cerebral artery aneurysm is rare vascular lesion and few cases have been reported in the literature. Microsurgical clipping is applied to treat a giant middle cerebral artery aneurysm .A 26 year-male presented with complain severe headache, multiple episodes of vomiting and one episode of sudden loss conscious since few hours prior to admission at emergency department. Cerebral Angiography showed a giant saccular middle cerebral artery (MCA) aneurysm. A standard right pterional approach applied to expose MCA and microsurgical clipping was performed. No any serious neurological complication was noted after surgery except right facial palsy. Patient was discharged at the 12th day of surgery.Endovascular therapy as well as STA-MCA bypass surgery plus clipping are usually applied to manage the giant MCA aneurysm. However, alone microsurgical clipping is also effective and has better result.